Dysfunctional cerebellar Purkinje cells contribute to autism-like behaviour in Shank2-deficient mice - Saša Peter (Nature Portfolio, 2016)
Mutations in SHANK2 are associated with autism spectrum disorders (ASD). Here, Peter et al. show that selective loss of Shank2in Purkinje cells of the mouse cerebellum leads to deficits in plasticity, motor behaviour, and a social behaviour phenotype similar to that seen in ASD.